Macro and microscopic study of the pineal gland of the adult alpaca (Vicugna pacos) - Westreicher Diaz, Mitzi Deana (2022)
The study aimed to describe the anatomy of the pineal gland of the adult alpaca. It was used 10 pineal glands from five male alpacas and five female alpacas obtained in September 2019 from culled alpacas benefited in the Huancavelica abattoir, Peru. The macroscopic evaluation consisted of the in-situ description and its relationship with the adjacent structures, as well as taking its measurements (length, width and thickness). Hematoxylin-Eosin and Masson's Trichrome stains were used for microscopic evaluation. The pineal gland is in the epithalamus, in the middle of the cerebral hemispheres in a dorsal-caudal direction, between the habenular and posterior commissure. It does not have lobes and the shape is like pine or pea. The glands of the males are longer and thicker while those of the females are wider. The pineal glands are classified as subcallosal and type A or proximal. Histologically, the parenchyma lacks differentiation between cortex and medulla and it is highly vascularized. Cellularly, pinealocytes and neuroglia are mainly distinguished, and pigments, pigment cells and calcifications can also be found.